The effects of graded caloric restriction: XII. Comparison of mouse to human impact on cellular senescence in the colon. Issue 3 (25th March 2018) - Fontana, Luigi; Mitchell, Sharon E.; Wang, Boshi; Tosti, Valeria; van Vliet, Thijmen; Veronese, Nicola; Bertozzi, Beatrice; Early, Dayna S.; Maissan, Parcival; Speakman, John R.; Demaria, Marco
Summary: Calorie restriction (CR) is an effective strategy to delay the onset and progression of aging phenotypes in a variety of organisms. Several molecular players are involved in the anti‐aging effects of CR, but mechanisms of regulation are poorly understood. Cellular senescence—a cellular state of irreversible growth arrest—is considered a basic mechanism of aging. Senescent cells accumulate with age and promote a number of age‐related pathologies. Whether environmental conditions such as diet affect the accumulation of cellular senescence with age is still unclear. Here, we show that a number of classical transcriptomic markers of senescent cells are reduced in adult but relatively young mice under CR. Moreover, we demonstrate that such senescence markers are not induced in the colon of middle‐age human volunteers under CR in comparison with age‐matched volunteers consuming normal Western diets. Our data support the idea that the improvement in health span observed in different organisms under CR might be partly due to a reduction in the number of senescent cells.